2020
DOI: 10.1371/journal.pone.0228495
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of zolpidem use in France halved after secure prescription pads implementation in 2017: A SNDS database nested cohort study

Abstract: Our objective was to quantify the impact on the use of zolpidem of the obligation implemented in France in 2017 to use secure prescription pads to prescribe it. We conducted a cohort study within the French SNDS healthcare database. Patients aged over 18 years of age were considered for inclusion. The number of prevalent users and incident episodes of zolpidem use were compared before the change in law (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Despite these two limitations, we can assume that this legal framework reduced the consumption of zolpidem and so should have beneficial effects, such as the reduction of side effects related to zolpidem, especially in young occasional consumers. Our results showed a decrease in the use of zolpidem, and are in agreement with those of other authors who have worked on this question [20,[34][35][36]; however, we also showed that this decrease was different according to the age. For patients over 65 years old, the measure was less effective overall.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite these two limitations, we can assume that this legal framework reduced the consumption of zolpidem and so should have beneficial effects, such as the reduction of side effects related to zolpidem, especially in young occasional consumers. Our results showed a decrease in the use of zolpidem, and are in agreement with those of other authors who have worked on this question [20,[34][35][36]; however, we also showed that this decrease was different according to the age. For patients over 65 years old, the measure was less effective overall.…”
Section: Discussionsupporting
confidence: 93%
“…The French national ZORRO study (ZOlpidem and the Reinforcement of Regulation of prescription Orders) [20], a study which aim to measure the impact of the implementation of the regulatory framework concerning the zolpidem in France, showed a decrease in prevalence of zolpidem users in general population. However, older people were not specifically studied, as it is common for them to be dependent [4].…”
Section: Introductionmentioning
confidence: 99%
“…This decreased prevalence seemed to be mainly due to a high number of treatment discontinuations after the measure: 4.3 times higher than the number of treatment initiations. 11 Among users who have discontinued zolpidem use, two situations can be distinguished: either they have completely stopped using sedatives and hypnotics or they have started using other medications.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, French regulations for zolpidem prescription impose the use of secure prescription booklets, a thorough specification of dosage and quantity, and maximal 4 weeks treatment duration. 46 An evaluation of these measures has demonstrated efficacy, with a drastic decrease of zolpidem use in the general population. 46 This might be an interesting lead for future health policies in our country.…”
Section: Discussionmentioning
confidence: 99%
“… 46 An evaluation of these measures has demonstrated efficacy, with a drastic decrease of zolpidem use in the general population. 46 This might be an interesting lead for future health policies in our country.…”
Section: Discussionmentioning
confidence: 99%